CAROTID ATHEROSCLEROSIS ACCORDING TO THIGH AND WAIST CIRCUMFERENCE IN PREDIABETIC PATIENTS - Kim, Chul Sik; Jang, Seol A; Kim, Kyoung Min; Park , Seok Won (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Patients with diabetes are at a higher risk for cardiovascular diseases. Even patients with prediabetes have increased cardiovascular risk, and preventive measures are necessary. It is known that the thinner the thighs and the larger the waist circumference, the higher the risk of cardiovascular disease. Several studies have shown that thigh and waist circumference are associated with atherosclerosis in diabetic patients. METHODOLOGY This study investigated the relationship of thigh and waist circumference with carotid atherosclerosis in patients with prediabetes. This observational study included 337 Korean subjects with prediabetes, in whom anthropometric measurements and carotid ultrasonography were conducted. Carotid plaque was defined as focal structures encroaching the arterial lumen by ≥0.5 mm or 50% of the surrounding intima-media thickness (IMT) value or a thickness ≥1.5 mm. RESULTS As a result of the analysis, there was no relationship between carotid atherosclerosis and thigh and waist circumference in both men and women with prediabetes. CONCLUSION Results suggest that the relationship between cardiovascular risk and body type measured by thigh and waist circumference is unclear and may vary depending on glycemic status. However, further longitudinal studies are warranted.